2007
DOI: 10.1080/10673220701679812
|View full text |Cite
|
Sign up to set email alerts
|

Neuroreceptor Imaging Studies in Schizophrenia

Abstract: The ability of SPECT and PET to image specific biomolecules in the living brain provides a unique tool for clinical researchers. It is therefore not surprising that the use of neuroreceptor-imaging techniques has become more widespread over the past decade. This article reviews the application of these techniques to the study of schizophrenia. The design of neuroreceptor-imaging studies performed in the field of schizophrenia research can be broadly divided into two categories: (1) studies of pathophysiology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 244 publications
(149 reference statements)
1
19
1
Order By: Relevance
“…For example, some, though not all, post mortem studies have detected an increase in the level of dopamine in the striatum or an increase, even in unmedicated patients, in the levels of the dopamine metabolite HVA (for a review, see Davis et al, 1991). This is consistent with the numerous findings of an increase in striatal uptake of dopamine in patients with schizophrenia, as determined by an increase in the uptake of Fluoro-Dopa, by the dopamine-synthesizing enzyme L-amino acid decarboxylase (Frankle, 2007; Hietala et al, 1999; Hietala et al, 1995; Lindström et al, 1999; Meyer-Lindenberg et al, 2002; Reith et al, 1994). Similarly, PET imaging has also found that in patients with schizophrenia, there is an increase in the striatum of amphetamine-induced displacement of D2 receptor binding, consistent with increased dopamine release (Abi-Dargham et al, 1998; Breier et al, 1997; Laruelle et al, 1996).…”
Section: A Dopaminergic Hyperfunction In the Striatum As Causal In Thsupporting
confidence: 92%
“…For example, some, though not all, post mortem studies have detected an increase in the level of dopamine in the striatum or an increase, even in unmedicated patients, in the levels of the dopamine metabolite HVA (for a review, see Davis et al, 1991). This is consistent with the numerous findings of an increase in striatal uptake of dopamine in patients with schizophrenia, as determined by an increase in the uptake of Fluoro-Dopa, by the dopamine-synthesizing enzyme L-amino acid decarboxylase (Frankle, 2007; Hietala et al, 1999; Hietala et al, 1995; Lindström et al, 1999; Meyer-Lindenberg et al, 2002; Reith et al, 1994). Similarly, PET imaging has also found that in patients with schizophrenia, there is an increase in the striatum of amphetamine-induced displacement of D2 receptor binding, consistent with increased dopamine release (Abi-Dargham et al, 1998; Breier et al, 1997; Laruelle et al, 1996).…”
Section: A Dopaminergic Hyperfunction In the Striatum As Causal In Thsupporting
confidence: 92%
“…Some, but not all, investigations of second-generation antipsychotics report increased receptor binding in extrastriatal regions compared with striatal binding (Frankle, 2007). All PET studies describing this preferential extrastriatal binding effect have been performed using FP as the radioligand.…”
Section: Discussionmentioning
confidence: 99%
“…Other chapters in this volume will discuss metabolic and structural imaging. We also refer readers to Frankle's recent review of neuroreceptor imaging studies in schizophrenia (Frankle 2007; see also Urban and Abi-Dargham, this text). Readers interested in the technical details of the functional imaging methods used in the studies reviewed are referred to Andreasen (1989) especially for its excellent chapters on single-photon emission computed tomography (SPECT) and positron emission tomography (PET), to Wood (1987) for descriptions of cerebral blood flow (CBF) methods, and to Buxton (2009) and Huettel et al (2009) for descriptions of functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 97%